3D dendritic-Fe2O3@C nanoparticles as an anode material for lithium ion batteries. Issue 30 (27th March 2017) - Zhang, Xiaohua; Zhou, Zhongfu; Ning, Jinyan; Nigar, Salma; Zhao, Tingkai; Lu, Xionggang; Cao, Huaqiang
Abstract : 3D dendritic Fe2 O3 nanoparticles wrapped with carbon (denoted as 3DD-Fe2 O3 @C hereafter) were synthesized. Abstract : 3D dendritic Fe2 O3 nanoparticles wrapped with carbon (denoted as 3DD-Fe2 O3 @C hereafter) were synthesized. It is found that the 3DD-Fe2 O3 @C is composed of α-Fe2 O3 and amorphous carbon. As an anode material for lithium ion batteries (LIBs), it exhibits an excellent discharge/charge capacity (982 mA h g −1 and 971 mA h g −1 after 100 cycles at a rate of 100 mA g −1 ), and good cyclic stability and rate capability.